EVALUASI PROGRAM LEMBAGA MODEL DESA KONSERVASI (LMDK) DAN IMPLIKASINYA TERHADAP KESEJAHTERAAN MASYARAKAT DI DESA LINGGASANA KECAMATAN CILIMUS KABUPATEN KUNINGAN - Khusnul Khotima (UIN Siber Syekh Nurjati Cirebon, 2016)
The Village Model Conservation (LMDK) is one Kemenhut policy aimed at villagers it is or society be around conservation area. LMDK occurs when the transition the region the area Ciremai be a national park on 19 October 2004. One village supporting get programs lMDK is a Village Linggasana in Cilimus district brass.Methods used in this research is deskriptif-kualitatif. Technique withdrawal informants by using purposive and using three technique data collection, namely observation, interview and documentation. Analysis in this research uses the data analysis in the field model miles and huberman, by do reduction data, presentation of data and verification or withdrawal conclusion. After data collected, so the next step is to triangulate it or merger. The result of this research indicates that program LMDK that existed in the Village Linggasana are. This is because several factors, whether it is a factor of the community and from the his government itself. But basically, not functioning LMDK the program was misstated the government in designing programs empowerment for the village buffer, and the LMDK that existed in the village linggasana does not fully answers the needs of the people Linggasana itself. Keywords: evaluation, implementation, implications, welfare, lMDK program